Influence of Synthesis Process on the Colour Properties of Mixed Oxide Pigment Bi1.5Zn0.5Ce2O7 - Těšitelová, Kateřina; Šulcová, Petra; Kaufmannová, Milena (My University, 2016)
The main attention in this research was focused on the yellow shade pigment synthesis based on Bi2O3 doped by zinc and cerium ions. The goal was to suggest and elaborate the different synthesis conditions of the studied pigment Bi1.5Zn0.5Ce2O7, investigate its colour possibilities and verify its applicability.
Vliv způsobu syntézy na barevné vlastnosti směsného oxidického pigmentu Bi1.5Zn0.5Ce2O7
Keywords: Inorganic Pigments; Mixed Oxide Pigments; Bismuth Comounds; Colour Properties; Yellow Shade; anorgnaické pigmenty; směsné oxidické pigmenty; sloučeniny bismutu; barevné vlastnosti; žlutý odstín